MULTI-STAGES HYBRID FLOW SHOP SCHEDULING MODEL USING LOT STREAMING METHOD - IBNU ABI SYAHPUTRA (NIM : 23411009); Pembimbing : Dr. Anas Ma'ruf, SAID
This study discusses multi-stages hybrid flow shop scheduling with multiple non- identical machines at each stage. A setup time is considered before processing each sublot on a machine. A model of Mixed Integer Non Linear Programming (MINLP) has been proposed in this study. The objective function in the proposed model is to minimize the mean maximum completion time jobs. The method used to solve these problems is a lot streaming. Lot streaming is the process to break or splite a job into several sub-lots. The outputs of the model are job sequence, sublot size and machine allocation of each. The uniqueness of the proposed models is the ability for lot streaming in multiple non-identical machines problemin HFS scheduling. Several scenarios of the hybrid flow shop scheduling problem are defined for investige acuration and feasiblity of proposed model. Based on numerical testing, computational results indicate that the proposed model can solves the hybrid flow shop problem properly. In another hand, the proposed model needs a extra time to solve the huge number of unit sublot.